Constitutional Complaint and the Protection of Citizens the Constitutional Rights - I Dewa Gede Palguna (Constitutional Review, 2017)
Constitutional complaint is one of important issues to be dealt with by severral countries issues adopting constitutional court in their national legal system and the Federal Constitutional Court Germany (Bundesverfassungsgericht) is considered by expert as one of the most advance mechanism among countries in dealing with the issue. Generally speaking, constitutional complaint can be described as a complaint or lawsuit filed by an individual citizen who deems his or her constitutional right (s) has been violates by act or omission of public institution or public official. Mostly, such a complaint can only be filed it theere is no other legal remedy available or all legal remedies available have been exhausted. The Constitutional Court of The Republic of Indonesia however is not entrusted with authority to hear constitutional complaint case not withstanding the fact that statistical data on judicial review cases filed by many petitioners before the Court were substantially constitutional complaint issues. It means that, empirically giving the Court to hear constitutional complaint case is necessarily pivotal and theoritically, the Court has the very foundation to be entrusted withq such authority. Considering the complex mechanism to amend the Constitution of 1945, which exhaustively deserible the court’s authorities, this article offers the lawmaker a theoretical insight tio give the Court a limited authority to hear constitutional complaint case by the way of amending the law on Constitutional Court.